Model Pembelajaran kooperatif Tipe STAD sebagai Upaya Meningkatkan Hasil Belajar Siswa pada Materi Barisan dan Deret Bilangan di Kelas IX SMP Negeri 1 Labuhanhaji Aceh Selatan - Bintang Zaura; . Sulastri (Jurnal Peluang, 2012)
Abstract One of the lesson while student have to learn it there are ranks and line aritmatics number. Base from that, writer do research with purpose know are the cooperative learning model STAD type can improve learning result in the ranks and line aritmatics number in class IX SMPN 1 Labuhanhaji South Aceh and for know the students activies during the learning process with cooperative learning model STAD type in ranks and line aritmaticsc number at class IX SMPN Labuhanhaji South Aceh. Subject that take from the research are students at class IX4 SMPN 1 Labuhanhaji South Aceh. Data was collected by do test and observation when learning implementation that do in two cycle activity. Data analysis in this research use statistic descriptive technic that is determine the average of the test every in the end of the syclus with count the presentase the students learning success. The result research show that model application of cooperative learning STAD type can during learning at ranks and line aritmetics at class IX SMPN 1 Labuhanhaji South Aceh. This thing can see from the raising completeness learning in every siclus. Clasical completeness in siclus I is 81,82% with the average value 79,24, classical completeness in siclus II is 90.91% with average value 86,21 or increase 8,08% equivalent with average value in siclus I. Research result show too that students activities the during learning with cooperative model STAD type in ranks and line aritmatics number at class IX SMPN 1 Labuhanhaji South Aceh more active. That thing sign with active students that focus on the teacher’s explanation, active student group discussion, the braveness of students in questioning, answer quation and comprehend subject.Keywords: The Cooperative Type STAD, result student learning